Cellulose agro-waste for potential bio-packaging - Mohd Ali, Noor Saadiah; Saidin, Nurhafizah; Jamaudin, Rosmaya; Jemain, Siti Fathimah Putery; Ismail, Nur Farrah Syazwanie; Wan Ahmad, Wan Khairi (Faculty of Applied Sciences Universiti Teknologi MARA, 2024)
because of storage and transportation issues, pointing out inequalities in packaging systems. Packaging remained an important factor in ensuring the quality of packed food products. It had been refined from time to time to provide a standard. Parallel to the introduction of the National Green Technology Policy by the government of Malaysia on alternatives to solve energy and environmental issues through green technology, it is our interest to develop a new class of materials from agro-waste sources that can contribute towards the advancement of eco-friendly and sustainable materials for packaging applications with enhanced barrier, thermo-mechanical, rheological, and antimicrobial properties. The bio-packaging was designed using cellulose-based biodegradable films. The biofilm was evaluated based on the mechanical, structural, surface, and chemical properties to confirm the suitability of the biofilm as food packaging. Different fruits and vegetables were packed in a container in three different environments: 1) control, 2) covered with PE film, and 3) covered with biofilm. It was observed that the samples packed with the biofilm demonstrated better freshness and lower moisture content than that of the control and container with PE. Naturally, renewable materials used in this work can replace current synthetic plastic and can be commercialized in the environmentally friendly food packaging market.